2021
DOI: 10.3390/ph14080773
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of TRKB Activation by the Angiotensin II Receptor Type-2 (AT2R) Agonist C21

Abstract: Blockers of angiotensin II type 1 receptor (AT1R) exert antidepressant-like effects by indirectly facilitating the activation of the angiotensin II type 2 receptor (AT2R), which leads to increased surface expression and transactivation of tropomyosin-related kinase B receptors (TRKB). Compound 21 (C21) is a non-peptide AT2R agonist that produces neuroprotective effects. However, the behavioral effects of C21 and its involvement with the brain-derived neurotrophic factor (BDNF)-TRKB system still need further in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…No genotype effect of Y433F mutation was observed in the ability to discriminate between conditioned and unconditioned contexts [interaction: F(1,15)=0.6472; P=0.4337; trial: F(1,15)=45.87; P < 0.0001; genotype: F(1,15)=0.5711, P=0.4615; N=8,9], figure 4B. For comparison, BDNF.het mice have compromised performance in this test [interaction F(1,10)=6.745, P=0.0266; trial: F(1,10)=15.64, P=0.0027; genotype: F(1,10)=12.57, P=0.0053; N=6/group], figure 4C, as observed previously (Laukkanen et al, 2021), as well as in the extinction of conditioned fear (Karpova et al, 2011).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…No genotype effect of Y433F mutation was observed in the ability to discriminate between conditioned and unconditioned contexts [interaction: F(1,15)=0.6472; P=0.4337; trial: F(1,15)=45.87; P < 0.0001; genotype: F(1,15)=0.5711, P=0.4615; N=8,9], figure 4B. For comparison, BDNF.het mice have compromised performance in this test [interaction F(1,10)=6.745, P=0.0266; trial: F(1,10)=15.64, P=0.0027; genotype: F(1,10)=12.57, P=0.0053; N=6/group], figure 4C, as observed previously (Laukkanen et al, 2021), as well as in the extinction of conditioned fear (Karpova et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…Context Discrimination Task -CDT. Male TRKB.Y433F mice and their TRKB.wt littermates were submitted to context discrimination task as described previously (Michels et al, 2018;Laukkanen et al, 2021). Briefly, the animals were acclimated to the experimental room for 1h, following 5 min habituation to the experimental chamber, the animals received 3 scrambled shocks (0.6mA/2s, intervals 30s-1min) in context A (conditioning, transparent walls, LxWxH: 23×23×35cm, with metal grid bottom) followed by a 2min period without any shocks.…”
Section: Behavioral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies from our lab and others have demonstrated AT2R's role in fear extinction (11,18,70). This, as well as its direct translation to exposure-based PTSD therapies in humans (33,44,45), showed extinction learning as an ideal model for assessing the functional effect of AT2R on fear memory.…”
Section: Discussionmentioning
confidence: 86%
“…The behavioral effects that we see with mPFC AT2R deletion may additionally be dependent on a TrkB/BDNF signaling pathway, as there is emerging evidence that cortical AT2R is dependent on co-expression with TrkB to influence learned fear (18,70,72). Further studies will directly interrogate the electrophysiological impact of AT2R activation or deletion on somatostatin interneuron activity and mPFC projections, as well as whether chemogenetic activation of AT2Rexpressing mPFC interneurons can rescue or facilitate fear extinction.…”
Section: Discussionmentioning
confidence: 86%